2020
DOI: 10.1002/rcs.2170
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of robotic‐assisted versus conventional unicompartmental knee arthroplasty for the treatment of single compartment knee osteoarthritis: A meta‐analysis

Abstract: Background The robotic‐assisted unicompartmental knee arthroplasty (UKA) is proposed to improve the accuracy of component positioning. Methods We conducted a literature search in Medline, Embase, Web of Science and the Cochrane Library until April 2020. Results Our meta‐analysis included 10 articles, involving 1231 knees. Our meta‐analysis demonstrated that the robotic group had significantly better results in outliers of limb alignment (p < 0.001) and outliers of tibial alignment (p < 0.001). No statistical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…1). In all ten meta‐analyses, conventional knee arthroplasty was considered the control group; three analysed outcomes of robot‐assisted UKA [12, 47, 48], six analysed outcomes of robot‐assisted TKA [1, 13, 20, 28, 32, 35], and one analysed outcomes of both robot‐assisted UKA and TKA [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). In all ten meta‐analyses, conventional knee arthroplasty was considered the control group; three analysed outcomes of robot‐assisted UKA [12, 47, 48], six analysed outcomes of robot‐assisted TKA [1, 13, 20, 28, 32, 35], and one analysed outcomes of both robot‐assisted UKA and TKA [7].…”
Section: Resultsmentioning
confidence: 99%
“…One meta‐analysis [7] included 13 studies on UKA, one of which [31] did not report on robotic assistance, but instead compared patient‐specific to conventional instrumentation in terms of postoperative knee alignment and knee society score (KSS). One meta‐analysis was found to be of “good quality” [48], and three were found to be of ‘critically low quality’ due to weaknesses in more than two critical domains [7, 12, 47] (Table 2, Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The workspace of the robot is specifically adapted for unicompartmental knee arthroplasty considering inherent safety. The objective is to provide a versatile robotic tool which improves the accuracy of implant positioning and reduces the revision rate, as reported in literature [ 17 , 19 , 20 ], while optimizing its integration into the conventional surgical workflow.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have found improved complication rates with computer-assisted patellofemoral arthroplasty and unicompartmental knee arthroplasty (CA-UKA), others have found no difference. 1215 There are minimal data regarding outcomes of computer-assisted patellofemoral arthroplasty and computer-assisted bicompartmental knee arthroplasty (CA-BKA). 1618…”
mentioning
confidence: 99%